(untitled) (Architecture Image Studies, 2025)
This study explores the integration of Amanah (trustworthiness) within the concept of financial solvency to enhance corporate financial performance. Drawing upon Capital Structure and Trade-Off Theories, it develops a new paradigm called Amanah Financial Solvency (AFS), a fusion of financial prudence and Islamic ethical stewardship. Through a comprehensive literature review from Scopus, WoS, ScienceDirect, and Emerald databases, this study reveals that Amanah transforms solvency from a mere financial ratio into a moral construct grounded in accountability, transparency, and integrity. Theoretically, AFS extends traditional solvency frameworks by embedding moral consciousness into financial decision-making. Empirically, it bridges inconsistencies in solvency performance relationships by introducing Amanah as a moderating factor. The study concludes that sustainable financial performance arises not only from rational optimization but also from the ethical equilibrium between profitability, responsibility, and divinity.